PERAN ORANG TUA TERHADAP KONSUMSI ALKOHOL PADA REMAJA PUTRA DI DESA SIDOREJO KECAMATAN SUGIO KABUPATEN LAMONGAN TAHUN 2015 - Amirul Amalia (Universitas Aisyiyah Yogyakarta, 2015)
The aim of research to determine the relationship of the role of parents on alcohol consumption in young men in the village Sidorejo Sugio subdistrict in Lamongan district in 2015. The study design used cross sectional analytic approach. The entire population of young men who consume alcoholic beverages in the village Sidorejo Sugio subdistrict in Lamongan district in June 2015 with Simple Random Sampling technique. Data taken with kuessioner and analyzed using Spearman Rank test with α = 0.05. The result showed almost half or 34.8% less than the role of parents, and more than 63% partially or low levels of alcohol consumption. There is a relationship between the roles of parents with alcohol consumption in young men in the village Sidorejo Sugio Lamongan District of the Year 2015. Rated rs = 0.749 and p = 0.000.Keywords: role of parents, adolescents, alcohol consumption